2006
DOI: 10.1021/jp056818u
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Study of Polarizable Ion Models for Molten AgBr

Abstract: Three different polarizable ion models for molten AgBr have been studied by molecular dynamics simulations. The three models are based on a rigid ion model (RIM) with a pair potential of the type proposed by Vashishta and Rahman for α-AgI, to which the induced dipole polarization of the ions is added. In the first (PIM1) the dipole moments are only induced by the local electric field, while in the other two (PIM1s and PIM2s) a short-range overlap induced polarization opposes the electrically induced dipole mom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 41 publications
5
51
0
Order By: Relevance
“…36-38 They were also used by Trullas and co-worker to study a series of silver and copper halides, [39][40][41][42][43] and the PIM model now is implemented in the CP2K code. 44 Going back to the case of oxides, when attention is restricted to a single phase or where similar materials are being compared it is often sufficient to neglect the full complexity of the AIM model, and we have also successfully used some PIM-type potentials in the case of amorphous GeO 2 45,46 and of doped zirconia crystals.…”
Section: Interaction Potentialsmentioning
confidence: 99%
“…36-38 They were also used by Trullas and co-worker to study a series of silver and copper halides, [39][40][41][42][43] and the PIM model now is implemented in the CP2K code. 44 Going back to the case of oxides, when attention is restricted to a single phase or where similar materials are being compared it is often sufficient to neglect the full complexity of the AIM model, and we have also successfully used some PIM-type potentials in the case of amorphous GeO 2 45,46 and of doped zirconia crystals.…”
Section: Interaction Potentialsmentioning
confidence: 99%
“…Although we used the rigid ion model in this study, if we consider a polarizable ion model, the cation diffusion would become large. However, polarization effects on NaI, RbI, and their mixture would be weak compared to silver (or cupper) halides [13][14][15][16][17][18][19][20] and zinc halides [21,22]. Ciccotti et al have reported that D Na and D I for pure NaI at 1081K are 9.4 × 10 -5 and 6.8 × 10 -5 cm 2 /s, respectively [3].…”
Section: " ! "mentioning
confidence: 99%
“…Consequently, the condition  + ~ 0 would be strictly applicable to the pair potentials +-(r) and ++ (r). From the considerations based on these facts, the polarizable ion model has been applied to AgBr and AgCl (Bitrián and Trullàs, 2006 ;Wilson et al, 1996).…”
Section: Polarizable Ion Modelmentioning
confidence: 99%
“…The theory that Bitrián and Trullàs (2006) have developed is effective to revise the rigid ion model to some extent. However, as we have pointed out in the previous section, such dispersion called the polarization catastrophe is ascribed to the fact that the iteration has been done disregarding that the inter ionic distance r ij is required to be much longer than the distance between the positive and negative dipole charges.…”
Section: Evaluation Of Polarizable Ion Model In the Previous Sectionmentioning
confidence: 99%
See 1 more Smart Citation